Chemical and nutritional evaluation of major genotypes of nectarine (Prunus persica var nectarina) grown in North-Western Himalayas - Jayarajan, Smruthi (J Food Sci Technol, 2019)
Nectarine is an important stone fruit after plum and peach. The area under peach cultivation is now getting replaced by nectarine due to its fuzzless nature and high nutritive value. Nectarines are juicy, delicious fruits having low calorific value and have high antioxidant capacity. In India, its cultivation is confined to North-Western and North-Eastern Himalayas. In this study, five major nectarine cultivars growing in India namely, ‘Silver Queen’, ‘Red Gold’, ‘Spring Bright’, ‘Independence’ and ‘Missourie’ were harvested at commercial maturity and analyzed for various chemical and nutritional aspects. Our results showed that there were quantitative differences among the genotypes in different parameters analyzed. The predominant sugar in nectarine was fructose which was highest in ‘Silver Queen’ (14.48 mg 100 g(−1) FW) and lowest in ‘Independence’ (9.04 mg 100 g(−1) FW). Major organic acids were malic, succinic, citric and acetic acid. The highest malic acid content was recorded in ‘Independence’ (1.13 mg 100 g(−1) FW) and lowest in ‘Red Gold’ (0.61 mg 100 g(−1) FW). Nectarine genotypes chiefly contained phloridizin dihydrate and chlorogenic acid as the phenolic component. However, chlorogenic acid was highest in ‘Spring Bright’ (17.63 µg g(−1) FW) and lowest in ‘Red Gold’ (3.67 µg g(−1) FW). Similarly, a wider variability was recorded in major and minor mineral concentrations among the genotypes. Based on these observations, it can be concluded that among the major nectarine varieties cultivated in India, ‘Silver Queen’ have higher mineral nutrients than other varieties, and ‘Spring Bright’ have higher phenolics and antioxidants.